PENGELOLAAN SARANA DAN PRASARANA DALAM PEMBELAJARAN TATAP MUKA DI MASA PANDEMI COVID-19 - Mufid Faruq Aziz; Ziwi Zelni; Asiyah Asiyah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
This study aims to describe the management of infrastructure at the Integrated Islamic Junior High School of Baitul Izzah Bengkulu in conducting face-to-face learning during the Covid-19 pandemic. This study is qualitative descriptive research. Data collection was done by interview, observation, and documentation. Data were analyzed through three steps, namely data reduction, data presentation, and drawing conclusions and verification. The results of this study explore the importance of needs analysis, source analysis, and priority analysis in formulating policies for planning infrastructure in schools so that the procurement of infrastructure is right on target. In addition, the school management system also supports the key role of principals in managing face-to-face learning infrastructure and ensuring that the maintenance process can be accounted for. This study also provides several implications for the management of facilities and infrastructure during the pandemic and is expected to provide enlightenment for other relevant stakeholders in dealing with face-to-face learning during the upcoming pandemic.